Model Kepengurusan Organisasi Dalam Meningkatkan Motivasi Kerja DKM Masjid Di Masjid Al-Furqon Haurgeulis - Sobirin, Sobirin; Zulhayti, Zulhayti; Afrig, Afrig (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Meanwhile, in general, a mosque is a holy place for Muslims that functions as a place of worship, a center for religious and community activities that must be fostered, maintained and developed in a regular and planned manner. The purpose of this research is to find out the management model of the Al-Furqon Haurgeulis Mosque DKM organization. The method used in this research is qualitative research with data collection techniques through observation, interviews and documentation. The Chairperson of the Mosque Prosperity Council is a driving force that encourages existing activities such as: 1) Providing motivation and direction to his subordinates. 2) Develop a work program 3) As a facilitator between activity units 4) Delegate tasks to subordinates 5) As an inspiration.Keywords: Mosque; Model; Motivation; Management AbstrakSecara umum masjid adalah tempat suci umat Islam yang berfungsi sebagai tempat ibadah, pusat kegiatan keagamaan, dan kemasyarakatan yang harus dibina, dipelihara dan dikembangkan secara teratur dan terencana. Tujuan penelitain ini adalah Untuk mengetahui model kepengurusan organisasi DKM Masjid Al-Furqon Haurgeulis. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Model Kepengurusan Organisasi dalam Meningkatkan Motivasi Kerja Dewan Kemakmuran Masjid Al-Furqon Haurgeulis. Ketua Dewan Kemakmuran Masjid adalah sebagai penggerak yang mendorong aktifitas kegiatan yang ada seperti: 1) Memberikan motivasi dan arahan kepada bawahannya. 2) Menyusun program kerja 3) Sebagai fasilisator antar unit kegiatan 4) Mendelegasikan tugas kepada bawahannya 5) Sebagai inpirator.Kata Kunci: Masjid; Model; Motivasi; Kepengurusan